Model of Land Use and Land Cover Change in Koto XI Tarusan District - Yatno, Triyatno; Ikhwan, Ikhwan; Febriandi, Febriandi (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
The article on models of land use change and land cover in Koto XI Tarusan District, Pesisir Selatan Regency, West Sumatra aims to model changes in land use and land cover in Koto XI Tarusan District, Pesisr Selatan Regency, and to find out the accuracy of the results of modeling changes in land use and land cover 2025 and 2030.The method used in this research is quantitative method using remote sensing data in the form of 2000 Landsat 5 images, 2009 Landsat 7 images, and 2019 Landsat 8 OLI images. The driving force used in this study is the distance from the road, the government center, health facilities, educational facilities, slopes, and elevations.The results showed that the results of modeling changes in land use and land cover in 2025 and 2030 indicated that there were changes in land cover of primary forest, secondary forest and mixed orchard. Land uses that have increased aruilt up area, and oil palm. The results of modeling accuracy test using the overall accuracy obtained in 2025 accuracy is 92.50 % and in 2030 is 89.75%. The accuracy results show that the modeling results have been very good.